Racism Issues Delivered in Lupin Film Series (2021) - Lubis, Rabitah Tasya Amaliah; Puspasari, Cindenia (Fakultas Dakwah UIN Saizu Purwokerto, 2023)
This study discusses the issue of racism in the Lupine film series on Netflix. Lupine is a two-season series that tells the story of a shrewd thief. This story is based on a famous white people novel in France. However, the director changed the lead character in this series by using black actors. The series was popular on Netflix due to the story and how the director brought a black man as the lead character in a high-level racist country. The main point that tries to be explained in this research is how the issue of racism is distributed through an action film series. The director wants to frame racism in France. This study is a qualitative interpretive study. The data source for this study is a film series titled Lupine, which aired on Netflix in 2021. The data collection method uses documentation studies of the selected sequence. Researchers determined 14 scenes and analyzed the scenes using Charles Sanders Peirce's semiotic model with Peirce's Trichotomy: sign, object, and interpretant. This study indicates an issue of racism that the director wants to represent through scenes showing racist behavior experienced by black people in France. All settings are categorized into indicators of racism which consist of stereotypes based on race, racial discrimination, and racial violence.